Pelatihan Media Pembelajaran Aplikasi Feliz Terintegrasi Framework MAS Darul Falah - Saragih, Sri Rahmah Dewi; Mapilindo, Mapilindo; Sirait, Azrai; Purba, Oktaviana Nirmala (Jurnal SOLMA, 2025)
Background: The transformation of education in the digital era requires educators to master innovative, practical, and integrated learning media, in line with global standards such as the UNESCO ICT Competency Framework for Teachers (2018). In reality, 35 teachers at MAS Darul Falah still face limitations in utilizing digital applications. To address this need, the community service team implemented a training program on the use of the Feliz application, integrated with a learning framework. Method: The activity was carried out using the Experiential Learning method, emphasizing hands-on practice. Although the intensive training session was conducted in one full day, the overall mentoring program ran for seven months to ensure sustainability. Evaluation indicators used quantitative instruments through pre-test and post-test on three competence aspects and structured observations. Results: The results showed a significant improvement in teachers’ skills in designing interactive learning media, with capability increasing from 15% to 70% (a 55% improvement). This concrete contribution was measured and demonstrated through the measurable increase in competence. The improvement in teachers’ self-confidence (from 25% to 80%) was analyzed using the concept of Self-Efficacy (Bandura). Conclusion: This program not only enhanced teachers’ competencies but also provided measurable contributions to the quality of the teaching and learning process at MAS Darul Falah.